Effect of hemodialysis on platelet function in end-stage renal disease Egyptian patients using in vitro closure time test (PFA-100 analyzer). (19th June 2014) - Mekawy, Mohamed A.; Habashy, Deena M. M.; Abd El-Mohsen, Waleed A. M.
Abstract: In patients with end-stage renal disease (ESRD), hemorrhagic complications are commonly encountered due to abnormalities in primary hemostasis, in particular, platelet (PLT) dysfunction and impaired PLT–vessel wall interaction. The pathogenesis of altered PLT function is considered multifactorial. Dialysis procedures had a favorable impact on bleeding complications in uremic patients. We aimed to evaluate the effect of hemodialysis on PLT function in patients with ESRD on a regular hemodialysis program. This study was carried on 40 ESRD Egyptian patients undergoing regular hemodialysis. Twenty healthy subjects were studied as a control group. Samples were assayed for PLT function by PLT function analyzer-100 (PFA-100) before and after the hemodialysis session. Prolonged closure time (CT) was found in 90% of patients before hemodialysis session and returned to normal ranges after hemodialysis session in 22% of those patients. The CT was longer among patients before and after hemodialysis session compared to controls ( p  < 0.01 and p  = 0.02, respectively), while it was shorter among patients after hemodialysis session compared to before hemodialysis session ( p  = 0.004). Hemoglobin (Hb) level and hematocrit (Hct) values were higher in control group compared to patient group before hemodialysis session ( p  < 0.01 and p  = 0.001, respectively), patients after hemodialysis session ( p  < 0.01 and p  = 0.02, respectively) and also in patients after hemodialysis compared to before hemodialysis session ( p  = 0.001 and p  < 0.01, respectively). The percentage change in PLT count was positively correlated with that of Hb ( p  = 0.01). We concluded that PLT dysfunction is encountered in ESRD Egyptian patients, and hemodialysis has the ability to correct some part of these hemostatic disturbances.